POTENSI KORIDOR JALAN YOS SUDARSO SEBAGAI RUANG TERBUKA DAN LANSEKAP KOTA PALANGKA RAYA - Mahdi Santoso, Noor Hamidah (Inersia : Jurnal Teknik Sipil dan Arsitektur, 2010)
ABSTRACTOne of important place in historic city of Palangka Raya is a big public openspace along the corridor of Yos Sudarso Street where various activities found here.Besides sport and social activities conducted in this place, many street vendors alsoarrised as well as green open space utilization. This paper is conducted to find out thepotentiality of Yos Sudarso corridor to be optimilized as public open space andimportant landscape in Palangka Raya by applying a concept approach research. Theconcept of public open space and landscape possible to come out by implementing aplanning concept of open space and re-arrange informal sector location andcompleting infrastructures such as garbage management , lighting system, and streetvendor stall design . Finally, a potential concept of green space need to balancingbetween vegetation and the presence of public building requirement to achievesustainable development and to reduce global warming impacts.Key words: Potential open space, landscape, Palangkaraya